CONSTRUCTING THE PSYCHOSOCIAL SPACE OF A NEIGHBOUR. THE GERMAN WEST AND THE RUSSIAN EAST IN POLISH REPORTAGES AND TRAVELLING PROSE IN RECENT YEARS - Gosk, Hanna (Porównania, 2012)
The text analyses selected, recently published, Polish reportage-travelogue prose on travels to Russia and Germany. It identifies their constitutive features, among others: the interpretive character of the message, narration the present from the perspective of the past, actualisation and redefinition of image stereotypes of the Russian and German. It poses a thesis that the therapeutic and compensating quality of these works locates them within enunciations operating post-dependence discourse.